Avaliação de hormônios gastrointestinais e leptina em pacientes com e sem reganho do peso após cinco anos da gastroplastia em y de roux - Saboya Sobrinho, Carlos Jose [UNIFESP] (2019)
OBJECTIVE: To evaluate and compare the role of gastrointestinal hormones – GHRELIN, peptide YY 3-36 (PYY 3-36), glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP), glucagon-like peptide-2 (GLP-2) - and LEPTIN in patients with and without weight regain undergoing Roux-en-Y gastric bypass after five years of the surgical procedure. METHODS: This is an observational, cross-sectional study, where 72 individuals divided into 3 paired groups: Group WR (WITH WEIGHT REGAIN): 24 patients undergoing Roux-en-Y gastric bypass with weight regain; Group WWR (WITHOUT WEIGHT REGAIN): 24 patients undergoing Roux-en-Y gastric bypass without weight regain and Group NO-OP (NON-OPERATED OBESE): 24 obese patients who are candidates for bariatric surgery. Patients with weight regain, defined as the increase of 5kg/m2 in BMI, taking as reference the minimum BMI reached during the postoperative period and the current BMI. The overall patients underwent clinical, biochemical, anthropometric and endoscopic evaluation. Hormone evaluation was performed in four settings – fasting, 30, 60 and 120 minutes - after standard meal intake, considering that the secretion of gastrointestinal hormones is affected by nutrient intake. RESULTS: For GLP-1, GLP-2 and PYY, values in the control group (NO-OP) did not change significantly. In the WR and WWR there was a sharp elevation at 30 minutes followed by a decrease at 60 and 120 minutes, ending with mean values still higher than baseline. Variations in ghrelin were not considered statistically significant. For GIP, the three groups showed similar behavior, with an increase at 30 minutes and a decrease at 60 and 120 minutes; however, in the overall evaluation (baseline period up to 120min), the WWR was the group in which GIP reached its lowest variation compared to baseline, and a statistical difference was found compared to the NO-OP and the WR groups. For leptin, the RW was similar to control, while the WWR showed significantly lower mean values. CONCLUSIONS: Non-operated obese individuals showed a postprandial secretion profile of PYY, GLP-1 and GLP-2, distinct from patients undergoing Roux-en-Y gastric bypass. In patients with weight regain, leptin concentrations were significantly higher when compared to patients without weight regain, thus suggesting a probable resistance to the action of this hormone. Patients without weight regain showed less variation in GIP, which implies a possible relation to the restoration of the secretory process after glucose control. GLP-1, GLP-2, PYY and GHRELIN showed no correlation with weight regain. Further studies should be conducted to better identify the mechanisms responsible for the findings reported by the current investigation, as well as clarifications on other conditions induced by Roux-en-Y gastric bypass.